2007
DOI: 10.1348/096317906x171037
|View full text |Cite
|
Sign up to set email alerts
|

Turnover intention and performance in China: The role of positive affectivity, Chinese values, perceived organizational support and constructive controversy

Abstract: This study examines antecedents of turnover intention and job performance in China. The total sample consisted of 153 employees in a toy manufacturing factory in South China. Data from matched supervisor and subordinate responses supported the hypotheses that the workplace experience of perceived organizational support related to turnover intention which in‐turn related to individual job performance. Findings also indicated that the employees with traditional values and positive affectivity related significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 49 publications
3
107
0
2
Order By: Relevance
“…The employee's perception of Human Resource or TMP (an antecedent to POS), become the basis for their perceptions of support from management and supervisors, which forms the foundation of their global perception of the organization's support (Veldman, 2012). Various studies have found that individuals with high POS will be less likely to seek and accept alternative employment (Allen, et al, 2003, Armstrong-Stassen & Ursel, 2009Dawley, et al, 2008;Harris, Harris & Harvey, 2007;Hui, Wong & Tjosvold, 2007;Jawahar & Hemmasi, 2006;Loi, et al, 2006;Riggle, Edmondson & Hansen, 2009). In addition, Allen et al (2003) has found that POS can act as the mediator of organizational supportive Human Resource Practices and the turnover process, and therefore indirectly of the employee's intention to quit.…”
Section: Perceived Organizational Support Talent Management Practicementioning
confidence: 99%
“…The employee's perception of Human Resource or TMP (an antecedent to POS), become the basis for their perceptions of support from management and supervisors, which forms the foundation of their global perception of the organization's support (Veldman, 2012). Various studies have found that individuals with high POS will be less likely to seek and accept alternative employment (Allen, et al, 2003, Armstrong-Stassen & Ursel, 2009Dawley, et al, 2008;Harris, Harris & Harvey, 2007;Hui, Wong & Tjosvold, 2007;Jawahar & Hemmasi, 2006;Loi, et al, 2006;Riggle, Edmondson & Hansen, 2009). In addition, Allen et al (2003) has found that POS can act as the mediator of organizational supportive Human Resource Practices and the turnover process, and therefore indirectly of the employee's intention to quit.…”
Section: Perceived Organizational Support Talent Management Practicementioning
confidence: 99%
“…8, No. 2;2015(Allen et al, 2013Hui et al, 2007;Miao, 2011). Previous empirical studies support that organizational support was related to job performance.…”
Section: Organizational Supportmentioning
confidence: 99%
“…Values play a functional role in work-related processes and outcomes, such as job satisfaction, organizational commitment, and work performance (Cohen, 2007;Cohen & Keren, 2008). They are predictors or moderators of these processes and criteria (Hui, Wong, & Tjosvold, 2007). Furthermore, they have an important role in establishing the fit between the individual and the organization.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%